Analysis of the “Third mission of universities” in the aspect of educational risks of digital divide - E. V. Voevodina (Цифровая социология)
The article analyses the “Third mission of universities”, which is understood as a set of socially signiﬁcant functions aimed at the individual and society development in a local (regional) focus. The relevance of the study is caused by the digital divide – a social phenomenon that manifests itself in the uneven development and digital technologies use by the population, depending on territorial and socio-demographic characteristics. Digital divide in the context of Russian reality is viewed as one of the types of educational risk, especially in relation to socially vulnerable population segments. It has been noted that universities can become “conductors” of digital transformations, they can contribute to the inclusion of people from “risk groups” into the digital society. The results of the study using the method of qualitative and quantitative documents analysis – Internet sites of Russian universities, their legal and regulatory documentation addressing the “third mission” have allowed us to conclude that Russian universities are focused on online education, massive open educational courses and training in digital professions. This circumstance is conﬁrmed by the ratings analysis “Three University Missions” (MosIUR) in 2020–2021. Educational programs aimed at mastering digital professions for socially vulnerable population groups are becoming widespread – they cover people of retirement and pre-retirement age, the unemployed, mothers with “small” children. Such programs provide for a budgetary ﬁnancing system and co-financing. However, the regional factor that affects the digitalisation level of the population, as well as its material well-being, is not taken into account. Hence, it has been concluded that it is necessary to expand the citizens list eligible for preferential training in digital professions. They should include poor people, small settlements residents in the periphery, crisis regions.